Synchronous Penile Metastasis from a High-Grade Adenocarcinoma of the Prostate - S. Dijkstra; A. G. van der Heijden; H. E. Schaafsma; P. F. A. Mulders (Case Reports in Urology)
Metastasis to the glans penis is a rare phenomenon and usually occurs in a late stage of disease. A 68-year-old man was referred to our clinic because of two indurated lesions of the glans penis and minor lower urinary tract symptoms. Digital rectal examination revealed a hard nodular prostate, and serum prostate-specific antigen (sPSA) level was 13.3 ng/mL. Biopsies of the penile lesions and transrectal ultrasound-guided prostate biopsies were taken. Immunohistochemical staining of formalin-fixed paraffin-embedded tissue exposed a synchronous penile metastasis from a high-grade adenocarcinoma of the prostate. Except a pathologically enlarged lymph node detected with MRI there was no suspicion on other metastases. Currently this patient is being treated with a Gonadoreline (GnRH) antagonist. Nevertheless, the prognosis will be poor.